NILAI-NILAI KEDAERAHAN DALAM MEMBANGUN KEPERCAYAAN MASYARAKAT - Sahlan Batubara (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
Cultural values embraced by the community basically become capital in building trust among fellow community members. Cultural values are revealed to be regional values, becoming a basic identity for every individual in society. So with the regional values that are the bridge in building community trust. Regional values become the basic values adopted by the local community, so to build community trust can not be separated from the basic values that have been embraced, and the basic values are regional values themselves.Keywords: Regional values, Community trust